Frontiers in Theoretical Analysis of Solid Electrolyte Interphase Formation Mechanism - Takenaka, Norio; Bouibes, Amine; Yamada, Yuki; Nagaoka, Masataka; Yamada, Atsuo (Advanced materials (Weinheim), 2021)
Solid electrolyte interphase (SEI) is an ion conductive yet electron‐insulating layer on battery electrodes, which is formed by the reductive decomposition of electrolytes during the initial charge. The nature of the SEI significantly impacts the safety, power, and lifetime of the batteries. Hence, elucidating the formation mechanism of the SEI layer has become a top priority. Conventional theoretical calculations reveal initial elementary steps of electrolyte reductive decomposition, whereas experimental approaches mainly focus on the characterization of the formed SEI in the final form. Moreover, both theoretical and experimental methodologies could not approach intermediate or transient steps of SEI growth. A major breakthrough has recently been achieved through a novel multiscale simulation method, which has enriched the understanding of how the reduction products are aggregated near the electrode and influence the SEI morphologies. This review highlights recent theoretical achievements to reveal the growth mechanism and provides a clear guideline for designing a stable SEI layer for advanced batteries. The nature of the solid electrolyte interphase (SEI) formed on battery electrodes governs the performance and safety of current and post‐Li‐ion batteries. However, it has been unclear how reaction products of an electrolyte interact and aggregate to form the final SEI. The morphological growth mechanism of the SEI, as revealed by state‐of‐the‐art theoretical simulation methodologies, is highlighted.